Solving delay differential equations by an accurate method with interpolation - Akgul, Ali; Kilicman, Adem (Hindawi Publishing Corporation, 2015)
We use the reproducing kernel method (RKM) with interpolation for finding approximate solutions of delay differential equations. Interpolation for delay differential equations has not been used by this method till now. The numerical approximation to the exact solution is computed. The comparison of the results with exact ones is made to confirm the validity and efficiency.